Pengaruh Situs Pembelajaran Online Terhadap Proses Pembelajaran Siswa Di Madrasah Aliyah Al-Bairuny Jombang - Fatoni Achmad; Risna Srinawati; Alivia Septa Pamungkas (MOMENTUM : Jurnal Sosial dan Keagamaan, 2020)
Abstract This study aims to determine the effect of online learning sites on the learning process of students at Madrasah Aliyah Al-Bairuny Jombang. The method used in this research is quantitative. This type of research is field research, while the data collection techniques use interviews and documentation. The results showed that online learning sites had an effect on the student learning process at Madrasah Aliyah Al-Bairuny Jombang. Of the thirty answers received, 74% of students used online learning sites, 16% sometimes used and 10% did not use online learning sites.